3D‐Printed Microelectrodes with a Developed Conductive Network and Hierarchical Pores toward High Areal Capacity for Microbatteries. Issue 2 (11th December 2018) - Zhou, Lin; Ning, Weiwei; Wu, Chen; Zhang, Dou; Wei, Weifeng; Ma, Jianmin; Li, Chengchao; Chen, Libao
Abstract: Microbatteries with a very narrow footprint require a high areal capacity to supply sufficient energy to power electronics. Here, 3D architected microelectrodes with high areal loadings are manufactured by 3D direct ink writing and freeze‐drying techniques to achieve high areal capacity for lithium‐ion microbatteries. The elaborate design of electrode configurations and the freeze‐drying treatment lead to hierarchical pores, which enhance the penetration of electrolyte and the transport of Li + . Meanwhile, the designed configurations prompt carbon nanotubes (CNTs) to form an interconnected conductive network in the whole electrode, thereby promoting fast electron transfer. As a result, the freestanding 3D‐printed lithium iron phosphate (LFP) microelectrodes show superior rate capacity and cycle stability compared to those of electrodes prepared through coating. The LFP microelectrodes still deliver an ultrahigh areal capacity of 5.05 mAh cm −2 after 100 cycles even with a higher areal loading of 32 mg cm −2, exhibiting a high capacity retention rate of 96.6%. Moreover, the full microbatteries assembled with the 3D‐printed LFP and lithium titanate (LTO) microelectrodes show good electrochemical performance. Abstract : 3D architected porous lithium iron phosphate (LFP) microelectrodes with high areal loading are prepared through the 3D direct ink writing (DIW) technique and freeze‐drying technique, and exhibit superior rate capability and cycle stability than coated electrodes, realizing an ultrahigh areal capacity of 5.05 mAh cm −2 . The full cells assembled with the 3D‐printed LFP and lithium titanate (LTO) microelectrodes show superior electrochemical performance.